[PP.01.02] CORRELATION OF PULSE WAVE ANALYSIS PARAMETERS WITH LEFT VENTRICULAR HYPERTROPHY, INTIMA-MEDIA-THICKNESS AND PLAQUES IN CAROTID ARTERIES IN A BRAZILIAN AMBULATORY CARE. (September 2016) - Resende, L.; Silva, M. A. V. Da; Resende, E. A. M. R.; Resende, J. A. M.; Silva, A. P. M. Da; Casemiro, A. L. M.; Lucas, R.M.
Abstract : Objective: To evaluate the correlation of pulse wave analysis parameters with left ventricular hypertrophy (LVH), Intima-media-Thickness (IMT) and plaques in carotid arteries. Design and method: 98 hypertensive or hypertension suspected patients seen in the academic hypertension ambulatory from the Federal University of Triangulo Mineiro (UFTM) between January and December 2015 had their pulse wave analysed by oscillometry - Mobil-O-Graph® PWA - EMI GmbH (Stolberg, Germany). Four consecutive measurements were taken every two minutes according to general recommendations for clinical studies of 'Clinical Applications of Arterial Stiffness, Task Force III: Recommendations for User Procedures (AJH 2002; 15: 445–452). All patients underwent two-dimensional echocardiography (ECO) and carotid ultrasound at Philipps iE33 Ultrasound equipment (Bothel, USA). Patients were categorized for the presence or absence of LVH in ECO according to Left Vetricular Mass Index (LVMI) values (Men > 115 g/m2, women > 95 g/m2), presence or absence of IMT > 0.9 in the right or left common carotid, presence or absence of plaques in the territory of the common and internal carotid. Pearson correlation coefficients were calculated with p values to evaluate the degree of association between variables. Results: Data from 98 patients were analyzed. The results are shown in Table 1. The correlation coefficient between the mean Pulse Wave Velocity (PWV) and the mean IMT was 0, 48, showing a significant correlation between these two variables. Regarding the presence of plaques in carotid arteries, there was a significant correlation with the PWV (r = 0, 38). Other parameters of the pulse wave analysis showed weak correlation with the IMT and the presence of plaques in carotid arteries. There was weak correlation between the LVH and all the parameters of the pulse wave analysis. Conclusions: The PWV correlated significantly with IMT and with the presence of plaques in carotid arteries. Other parameters of the pulse wave analysis showed weak correlations with LVH, IMT and plaques presence. Figure. No caption available.